2014
DOI: 10.1111/anae.12788
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of lidocaine to prevent laryngospasm in children: a systematic review and meta-analysis

Abstract: SummaryThe purpose of this meta-analysis was to determine the efficacy of lidocaine in preventing laryngospasm during general anaesthesia in children. An electronic search of six databases was conducted. The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines were adhered to. We included randomised controlled trials reporting the effects of intravenous and/or topical lidocaine on the incidence of laryngospasm during general anaesthesia. Nine studies including 787 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 62 publications
4
35
1
2
Order By: Relevance
“…although we excluded one study20 for no full text acquired and another study21 for adult patients enrolled. We got a result (RR = 0.39, 95% CI = [0.18, 0.86]) similar to that (RR = 0.34, 95% CI = [0.14, 0.82]) of Mihaha et al 19. in intravenous lidocaine vs. placebo group.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…although we excluded one study20 for no full text acquired and another study21 for adult patients enrolled. We got a result (RR = 0.39, 95% CI = [0.18, 0.86]) similar to that (RR = 0.34, 95% CI = [0.14, 0.82]) of Mihaha et al 19. in intravenous lidocaine vs. placebo group.…”
Section: Discussionsupporting
confidence: 83%
“…. For direct comparisons in topical lidocaine vs. placebo group, the risk ratio of laryngospasm is 0.37 [0.19, 0.72], similar to 0.42 [0.22, 0.80] given by Mihaha et al 19,. although we excluded one study20 for no full text acquired and another study21 for adult patients enrolled.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Previous studies suggested that laryngospasm was always occurred due to the increase of respiratory secretions, the mechanical irritations of endotracheal tube and the effects of anesthetic drugs, as well as the upper respiratory tract infections/potential infection and the suppression of mucociliary clearance by dry airflow during ventilation [6][7][8]. The occurrence of laryngospasm could bring rapid deterioration in systemic oxygenation and cyanosis, and decrease in surplus pulse O 2 (SpO 2 ), even become lifethreatening if some interventions were delayed [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Data shown in Fig. 1 are the results from a systematic review, where data from separate studies are plotted separately, and then all pooled together into a combined result [7]. Another way to meta-analyse data is to conduct a cumulative meta-analysis, where the results from the first study are plotted, then the results are pooled with the second study, then these two studies are pooled with the third one, and so on, so that changes as each study is added can be determined.…”
mentioning
confidence: 99%